Homely Pastorals versus the Unhomely Forest in The Lord of the Rings Trilogy and The Hobbit - Sikdar, Mahasweta (Literary Studies, 2024)
The representation of forests in British fantasy literature has changed with the changing dynamics of our relationship with the forest. The forest has been represented as many things- a place of redemption and trial, purity and temptation, mystery and adventure, freedom and exile; but it has not been represented as “home.” It is a liminal space between this world and the otherworldly; it is a place of enchantment. The protagonist must return home from the enchanted forest reborn or after a magical experience. The ‘enchanted forest’ is a leitmotif in Tolkien’s The Lord of the Rings Trilogy and The Hobbit, two seminal works in modern British fantasy. There are extensive studies of the forests of Tolkien (with a special focus on his iconic trees) and of the Shire as Tolkien's idealized England. However, the forests of Tolkien have rarely been studied as opposed to the idea of home. In this paper, I argue that Tolkien epitomizes the idea of a pastoral home through the Shire by constantly contrasting it with the ‘unhomely’ representation of forests. The article considers the cultural history of the British with their forest to understand why the forests are represented as ‘unhomely’ in the select texts. In this paper, I demonstrate that the two stories are ultimately tales of returning to a pastoral home after experiencing the enchantment that the forest has to offer.